2017
DOI: 10.1259/bjr.20160795
|View full text |Cite
|
Sign up to set email alerts
|

Use of patient outcome endpoints to identify the best functional CT imaging parameters in metastatic renal cell carcinoma patients

Abstract: Patient outcome was used to identify the best functional imaging parameters in patients with metastatic renal cell carcinoma. Taking patient outcome and reproducibility into account, BV, BV and BF provide the most clinically meaningful information, whereas PS seems to be treatment dependent. Standardization of acquisition protocols and post-processing software is necessary for future clinical utilization. Advances in knowledge: Taking patient outcome and reproducibility into account, BV, BV and BF provide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…We observed that early changes in BF and BV in advanced RCC patients were of greater magnitude in patients with stable disease compared to progressive disease. While we were unable to demonstrate statistical significance, our result is consistent with preclinical data in which successful anti-angiogenic treatment has been shown to inhibit VEGFR2, decrease tumor vessel number and density based on immunohistochemistry in xenograft and preclinical models [30,31,32,33]. In clinical studies of RCC, CT perfusion has been performed at five- and 10-week time points after initiating treatment, but we are the first to demonstrate that changes can be detected as early as eight days after treatment; however, whether early changes can reliably predict clinical outcome will need to be validated in a larger study.…”
Section: Discussionsupporting
confidence: 85%
“…We observed that early changes in BF and BV in advanced RCC patients were of greater magnitude in patients with stable disease compared to progressive disease. While we were unable to demonstrate statistical significance, our result is consistent with preclinical data in which successful anti-angiogenic treatment has been shown to inhibit VEGFR2, decrease tumor vessel number and density based on immunohistochemistry in xenograft and preclinical models [30,31,32,33]. In clinical studies of RCC, CT perfusion has been performed at five- and 10-week time points after initiating treatment, but we are the first to demonstrate that changes can be detected as early as eight days after treatment; however, whether early changes can reliably predict clinical outcome will need to be validated in a larger study.…”
Section: Discussionsupporting
confidence: 85%
“…All analyses were performed by a radiologist blinded to treatment and outcomes. Excellent interobserver correlations have been shown for this method ( 9 ).…”
Section: Methodsmentioning
confidence: 89%
“…Preliminary results have been published on 69 patients (DaRenCa-1, n = 50 and AIS, n = 19) evaluating various DCE-CT parameters ( 10 , 11 ) identifying BV as the best DCE-CT parameter using patient outcome as endpoint ( 9 ). For this study, more patients have been included, survival data has been updated, and all DCE-CT assessments have been fully repeated by an independent radiologist (ADN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations